Active fund management when ESG matters - Avramov, Doron; Cheng, Si; Tarelli, Andrea (Journal of Banking & Finance, 2026)
This paper develops and tests an equilibrium model of active fund management with ESG considerations. Heterogeneous sustainability preferences lead fund managers to intensify information acquisition on assets across the ESG spectrum, broadening the scope of active management. This information channel enhances price informativeness, lowers discount rates, and increases portfolio deviation from benchmarks. The model predicts a negative and concave ESG-expected return relation, stronger for green assets and weaker for brown assets. Using data on U.S. mutual funds and stocks from 2007–2021, we find supporting evidence based on price informativeness and the implied cost of equity capital.